The governance core school boards, superintendents, and schools working together - Campbell, Davis W.; Fullan, Michael (Corwin, 2019)
This book examines how local education governance- school boards in collaboration with district and school leadership- could, in every district, become an exemplar of highly effective decision-making, leadership and action.